2016
DOI: 10.1136/bmjopen-2016-011616
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of headaches on the quality of life of patients with glioblastoma multiforme: a qualitative study

Abstract: ObjectivesHeadaches and facial pain have been identified as the most prevalent form of pain among patients with glioblastoma multiforme, the most common malignant primary brain tumour. Despite this, minimal research has been undertaken investigating the direct and indirect impact these headaches have on their quality of life. Therefore, in this study, we aimed at gaining a personal insight into the importance and impact that these headaches have on the quality of life of patients with glioblastoma multiforme.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…This study also found that participants gained considerable satisfaction from being able to do “the little things” in life such as domestic tasks, which significantly helped them to maintain a sense of purpose and identity in a similar way to the participants in a study conducted by Sterckx et al 19 …”
Section: Discussionsupporting
confidence: 60%
“…This study also found that participants gained considerable satisfaction from being able to do “the little things” in life such as domestic tasks, which significantly helped them to maintain a sense of purpose and identity in a similar way to the participants in a study conducted by Sterckx et al 19 …”
Section: Discussionsupporting
confidence: 60%
“…The diagnosis of glioblastoma, after symptom presentation, is a grade 4 diagnosis with a prognosis of 15-18 months assuming aggressive medical intervention ( 5 ), Hemminger et al. ( 2 ) note a mean survival of 12.6 months.…”
Section: The Diagnosis Progression and Prognostications Of The Two Di...mentioning
confidence: 99%
“…Головний біль є інтегрованим показником виявів гіпертензійного та дислокаційного синдромів, що залежно від ступеня може суттєво впливати на якість життя і тактику лікування хворих. Отже, закономірно, що існує чіткий взаємозв'язок між головним болем та якістю життя хворих на ГБ [49].…”
Section: антиангіогенна терапія в клінічних дослідженнях у нейроонкологічних хворихunclassified